2021
DOI: 10.1021/acsnano.1c01552
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Graphene Microstructures Inspired by Honeycomb for Ultrahigh Performance Electromagnetic Interference Shielding and Wearable Applications

Abstract: High-performance electromagnetic interference (EMI) shielding materials with ultralow density, excellent flexibility, and good mechanical properties are highly desirable for aerospace and wearable electronics. Herein, honeycomb porous graphene (HPG) fabricated by laser scribing technology is reported for EMI shielding and wearable applications. Due to the honeycomb structure, the HPG exhibits an EMI shielding effectiveness (SE) up to 45 dB at a thickness of 48.3 μm. The single-piece HPG exhibits an ultrahigh a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 63 publications
1
74
0
Order By: Relevance
“…Figure b shows the main fabrication of the graphene electrode array. Our previous works have shown that the blue laser can induce commercial polyimide to generate a honeycomb graphene which has a larger and more regular pore size than the reported laser-induced graphene (LIG). , A blue laser with a laser beam of 300 μm and a wavelength of 450 nm was used in this work (details in the Methods). The designed graphene electrode array pattern was input into the computer to control the scanning path of the laser on the commercial polyimide film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure b shows the main fabrication of the graphene electrode array. Our previous works have shown that the blue laser can induce commercial polyimide to generate a honeycomb graphene which has a larger and more regular pore size than the reported laser-induced graphene (LIG). , A blue laser with a laser beam of 300 μm and a wavelength of 450 nm was used in this work (details in the Methods). The designed graphene electrode array pattern was input into the computer to control the scanning path of the laser on the commercial polyimide film.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are still challenges in the interconnection and protection of ultrathin bare GETs. , Consequently, it is of great significance to develop ultrathin, flexible, stretchable, and air permeable graphene electrodes with simple preparation. Laser-induced graphene, with its simple preparation, is widely used in wearable electronics, such as strain sensors, microfluidic biosensors, , electromagnetic interference shields, , multifunctional textiles, , etc. The development of a special transfer process combined with a laser induction process is helpful to realize the ultrathin graphene electrode for EOG signal acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…45 Previous research studies on EMI shields gradually tend to be more suitable for massive application scenarios, such as hightemperature resistance, [46][47][48][49][50][51] corrosion resistance, [52][53][54][55][56] transparency, [57][58][59][60][61] flexibility, [62][63][64][65][66][67] and wearable performance. [68][69][70][71][72] Song et al reported cellulose carbon aerogel@reduced graphene oxide (CCA@rGO) aerogel/polydimethylsiloxane composites exhibiting excellent EMI shielding performance with EMI shielding effectiveness (SE) up to 51 dB. 5 The skin-core structure of CCA@rGO aerogels contributes to great prospects for applications in lightweight, flexible EMI shielding composites.…”
Section: Introductionmentioning
confidence: 99%
“…Higher density metal grids will produce higher conductivity and thus better shielding effectiveness, but the light transparency also will be reduced. [ 28,29 ] Because of the low cost, good flexibility, and high chemical stability of carbon materials, scientists have conducted in‐depth researches on carbon materials, including carbon nanotubes, [ 39–41 ] carbon nanofibers, [ 31–34 ] carbon matrix composites, [ 42,43 ] and graphite nanosheets. [ 18–21 ] However, these reported conductive materials are generally based on thick carbon films or foams with poor light transmittance.…”
Section: Introductionmentioning
confidence: 99%